Neuroprotective properties of nutraceuticals in regulating neurodegenerative dementia / Nurul Ashikin Mazlan ... [et al.] - Mazlan, Nurul Ashikin; Mohd Nor Hazalin, Nurul Aqmar; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2022)
Dementia is a syndrome marked by a loss of mental abilities due to damage to at least one cognitive function, resulting in poor brain performance that compromises daily life activities. The multiple pathologic pathways underlying neurodegenerative dementia include protein misfolding, oxidative stress, neuro-inflammation, mitochondrial dysfunction, and calcium overload. The syndrome is a major concern to the healthcare system since the therapeutic options are limited and it has multiple adverse effects. Such therapeutic options function particularly to alleviate signs and symptoms. Recently, nutraceuticals have attracted significant attention due to their neuroprotective properties against dementia. However, few studies have focused on the mechanisms mediating the neuroprotective effects of nutraceuticals or their effectiveness against dementia, particularly in regulating neurodegeneration. Therefore, this review underlines the nutraceuticals used against dementia that includes omega-3 (PUFA), flavonoid, curcumin, resveratrol, and vitamins and to establish their neuroprotective mechanisms. The review covers relevant clinical trials demonstrating the effectiveness of nutraceuticals in supporting the possible treatment in neurodegenerative dementia. In conclusion, it is evident that certain nutraceuticals showed neuroprotective properties such as antioxidant, anti-inflammatory and anti-amyloidogenic. The findings will be useful when employing nutraceuticals in the management or treatment of dementia